The transcriptome dynamics of single cells during the cell cycle - Daniel Schwabe; Sara Formichetti; Jan Philipp Junker; Martin Falcke; Nikolaus Rajewsky (Molecular Systems Biology)
Abstract The cell cycle is among the most basic phenomena in biology. Despite advances in single‐cell analysis, dynamics and topology of the cell cycle in high‐dimensional gene expression space remain largely unknown. We developed a linear analysis of transcriptome data which reveals that cells move along a planar circular trajectory in transcriptome space during the cycle. Non‐cycling gene expression adds a third dimension causing helical motion on a cylinder. We find in immortalized cell lines that cell cycle transcriptome dynamics occur largely independently from other cellular processes. We offer a simple method (“Revelio”) to order unsynchronized cells in time. Precise removal of cell cycle effects from the data becomes a straightforward operation. The shape of the trajectory implies that each gene is upregulated only once during the cycle, and only two dynamic components represented by groups of genes drive transcriptome dynamics. It indicates that the cell cycle has evolved to minimize changes of transcriptional activity and the related regulatory effort. This design principle of the cell cycle may be of relevance to many other cellular differentiation processes.